Profesionalisme Guru Pengelolaan Sumber-Sumber Pembelajaran Pendidikan Agama Islam dalam Meningkatkan Mutu di SMPIT Mukhlisin Kabupaten Gowa - Muh. Imran Lukman; Muhammad Tang; St. Habibah (CV. Creative Tugu Pena, 2024)
Profesionalisme Teacher professionalism is a crucial factor in managing learning resources, especially in Islamic religious education. This study aims to identify the level of teacher professionalism in managing Islamic religious education learning resources at SMPIT Mukhlisiin Gowa Regency, analyse the factors that influence teacher professionalism, and evaluate its impact on improving the quality of education. The results showed that teacher professionalism in managing learning resources at SMPIT Mukhlisiin was at an adequate level. Some of the factors that influence teacher professionalism include academic qualifications, teaching experience, and support from the school. Teacher professionalism is proven to have a positive impact on the quality of education, characterised by improved student learning outcomes and the quality of the learning process. The conclusion of this study confirms the importance of improving teachers' professionalism in managing learning resources as an effort to improve the quality of Islamic religious education. Recommendations include providing continuous training for teachers, improving learning facilities and resources, and developing policies that support teacher professionalism.